The combined effects of topography and stiffness on neuronal differentiation and maturation using a hydrogel platform - Mattiassi, Sabrina (2023)
Biophysical parameters such as substrate topography and stiffness have been shown independently to elicit profound effects on neuronal differentiation and maturation from neural progenitor cells (NPCs) yet have not been investigated in combination. Here, the effects of various micrograting and stiffness combinations on neuronal differentiation and maturation were investigated using a polyacrylamide and N-acryloyl-6-aminocaproic acid copolymer (PAA-ACA) hydrogel with tunable stiffness. Whole laminin was conjugated onto the PAA-ACA surface indirectly or directly to facilitate long-term mouse and human NPC-derived neuron attachment. Three micrograting dimensions (2-10 µm) were patterned onto gels with varying stiffness (6.1-110.5 kPa) to evaluate the effects of topography, stiffness, and their interaction. The results demonstrate that the extracellular matrix (ECM)-modified PAA-ACA gels support mouse and human neuronal cell attachment throughout the differentiation and maturation stages (14 and 28 days, respectively). The interaction between topography and stiffness is shown to significantly increase the proportion of β-tubulin III (TUJ1) positive neurons and microtubule associated protein-2 (MAP2) positive neurite branching and length. Thus, the effects of topography and stiffness cannot be imparted. These results provide a novel platform for neural mechanobiology studies and emphasize the utility of optimizing numerous biophysical cues for improved neuronal yield in vitro.